Hacia una definición de activo ambiental: una propuesta desde la Contabilidad Tridimensional - Misse Ariza, Augusto (2021)
Traditional accounting of an economic-financial nature has developed the criteria for the recognition, measurement, valuation, presentation and disclosure of information of assets, based on the organizational control of resources and the generation of economic benefits from them, these judgments have been applied under the same guidelines to environmental assets. This research aim is to propose a concept of environmental asset based on an accounting for sustainability, based on an ethical vision that tends to defend life in conditions of dignity for the present and future generations of all forms and manifestations of life, recognizing the finite and limited condition of natural resources and their capacity to provide goods and services. The construction of a new definition of environmental asset required analyzing the established definitions, collect the significant and current aspects, improving its orientation and purpose from the recent progress of the care and conservation paradigms, as an ethical vision committed to life and its dignity.